Schistosoma “Eggs-Iting” the Host: Granuloma Formation and Egg Excretion - Schwartz, Christian; Fallon, Padraic G. (Frontiers in Immunology, 2018)
Schistosomiasis is a major cause of morbidity in humans invoked by chronic infection with parasitic trematodes of the genus Schistosoma. Schistosomes have a complex life-cycle involving infections of an aquatic snail intermediate host and a definitive mammalian host. In humans, adult male and female worms lie within the vasculature. Here, they propagate and eggs are laid. These eggs must then be released from the host to continue the life cycle. Schistosoma mansoni and Schistosoma japonicum reside in the mesenteric circulation of the intestines with egg excreted in the feces. In contrast, S. haematobium are present in the venus plexus of the bladder, expelling eggs in the urine. In an impressive case of exploitation of the host immune system, this process of Schistosome “eggs-iting” the host is immune dependent. In this article, we review the formation of the egg granuloma and explore how S. mansoni eggs laid in vasculature must usurp immunity to induce regulated inflammation, to facilitate extravasation through the intestinal wall and to be expelled in the feces. We highlight the roles of immune cell populations, stromal factors, and egg secretions in the process of egg excretion to provide a comprehensive overview of the current state of knowledge regarding a vastly unexplored mechanism.